DIGITAL GAME-BASED LEARNING MEDIA INNOVATION ON ROBOTIC TECHNOLOGY PROTOTYPE CREATION TO DEVELOP COMPUTATIONAL THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Nuril Ayyamil Izzah; Anggun Suwaibatulilla; Siti Khasfiyatin; Rina Tut Jayati; Supeno Supeno (Universitas Negeri Makassar, 2024)
The education sector plays a crucial role in preparing human resources to navigate and thrive in this digital era. One essential skill for adapting to the rapid technological advances is Computational Thinking (CT), which teaches students to frame problems as computational problems. However, the application of CT in learning practices in Indonesia has not been fully successful. This is evident from the 2021 PISA results, which highlight deficiencies in various CT-related competencies, including data practices, modeling and simulation practices, computational problem-solving practices, and systems thinking practices. Therefore, the education sector urgently needs innovative learning approaches that enhance student competencies to keep pace with technological developments. In response to this need, researchers have initiated the creation of innovative digital game-based learning media aimed at developing CT skills among junior high school students. The researchers employed the Research and Development (R&D) method, specifically using the ADDIE model. This digital game development aims to address the low CT proficiency among students in Indonesia. The resulting digital game-based learning media focuses on the topic of simple machines and is intended to be a valuable tool for teachers in fostering students' CT skills, ultimately preparing them to compete in the global workforce.